MODEL KURIKULUM PENGEMBANGAN DIRI DALAM MENINGKATKAN SIKAP SOSIAL PESERTA DIDIK SEKOLAH MASTER INDONESIA (SMI) DEPOK JAWA BARAT - Afifatunnisa Hanani; Akhmad Shunhaji; Khasnah Syaidah (STKIP Pesisir Selatan, 2026)
This study examines the implementation of a self-development curriculum model at Sekolah Master Indonesia (SMI) in Depok, West Java, and its impact on improving students' social attitudes. The purpose of this study is to evaluate how this curriculum affects social attitudes such as discipline, tolerance, responsibility, and self-confidence among students. The method used was qualitative with a descriptive thematic approach, involving observation, interviews, and documentation. The findings show that programmed activities such as counseling, English Club, BTQ, and Sanlat are effective in improving students' discipline and social tolerance. Unprogrammed activities such as collective prayer also contribute to the internalization of Islamic social values in daily life. Although there are challenges related to limited time and human resources, solutions such as integrating social activities into daily routines and improving the quality of educators help overcome these obstacles. This study recommends increasing the integration of social activities into the curriculum and improving the quality of educator training to support the sustainability of student character development. Overall, the implementation of the self-development curriculum at SMI Depok has had a positive impact on the development of students' social attitudes, with the potential to become a model for other schools in implementing a social-based character education curriculum.